Qualitative insights in item development for a comprehensive and inclusive measure of recovery capital. (2nd November 2022) - Bowen, Elizabeth; Irish, Andrew; LaBarre, Charles; Capozziello, Nicole; Nochajski, Thomas; Granfield, Robert
Abstract: Background: Item specification is foundational to measurement development but rarely reported in depth. We address this gap by explicating our use of qualitative methods to ground and develop items for a new recovery capital measure, the Multidimensional Inventory of Recovery Capital. Method: We recruited a diverse sample of service providers ( n  = 9) and people in recovery from alcohol problems ( n  = 23) to provide feedback on an item pool assessing social, human, physical, community, and cultural capital. Using applied qualitative analysis, we coded findings from interviews and focus groups and made final decisions by consensus regarding item elimination, retention, or revision. This process yielded a 49-item draft measure. Results: Only nine items from an initial 90-item list were retained in their original form. Participant feedback guided item elimination, addition, and revision for linguistic or conceptual clarity. We detected little systematic variation in feedback based on income or race; however, there were stark divergences on particular items based on recovery pathway (i.e. 12-step versus other approaches). Conclusions: The high degree of alteration to the item pool highlights the importance of establishing validity with respondents. Response variation based on recovery pathway suggests the need for broad heterogeneity in respondents. Measures that are sensitive, psychometrically sound, and aligned with theory are critical for advancing research on recovery capital and related disparities for diverse populations.